Modification of the Calculation of the Examination of the Platelet Count Using 1 Large Box of Leukocytes in the Improved Neubauer Counting Room - Zulfikar Ali Hasan; Nurdin Nurdin; Ridho Pratama; Artati Artati; Yaumil Fachni Tandjungbulu; Andi Fajrin Permana (Potekkes Kemenkes Makassar, 2023)
The direct examination of the platelet count using the improved Neubauer counting chamber is carried out by microscopic examination of 25 Medium Boxes of Erythrocytes, this method requires several field shifts so that more accuracy is needed when carrying out the examination. Modification of the calculation of the platelet count by using 1 large box of leukocytes in the improved Neubauer counting chamber requires only 1 field of view at the time of calculation so that it does not take a long time and is more thorough when carrying out microscopic platelet counts. The purpose of this study was to determine the number of platelets using the calculation of 25 squares while the erythrocytes and the number of platelets using a modification of the calculation of 1 large box of leukocytes. This type of research is a quasi-experimental which aims to determine the effect that arises due to certain treatments for examining the platelet count using 25 boxes while the erythrocytes and modification of the calculation using 1 large box of leukocytes. It was carried out at the Hematology Laboratory, Department of Medical Laboratory Technology, Poltekkes Kemenkes Makassar. This research was carried out to start in January-December 2022. Examination of the number of platelets in the counting chamber with 25 Medium Boxes of Erythrocytes and 1 Large Box of Leukocytes, from the 30 data obtained for each method after a different test using the Mann Whitney test obtained a significant p value of 0.234 > 0.05 so that it can be concluded that there is no difference in the number of platelets in 25 Medium Boxes of Erythrocytes and 1 Large Box of Leukocytes. This indicates that examination of the platelet count using 1 large box of leukocytes can be used as a manual examination method